1-{(E)-[3-(1H-Imidazol-1-yl)-1-phenylpropylidene]amino}-3-(2-methylphenyl)urea - Mohamed I. Attia; Mohamed N. Aboul-Enein; Nasser R. El-Brollosy; Seik Weng Ng; Edward R. T. Tiekink (Acta Crystallographica Section E, 2012)
In the title compound, C20H21N5O, the conformation about the imine bond [1.289 (3) Å] is E. Overall, the molecule is disk-shaped with the imidazole ring located above the remainder of the molecule and with the dihedral angles of 10.97 (15) and 12.11 (15)°, respectively, between the imidazole ring and the phenyl and methylbenzene rings; the dihedral angle between the aromatic rings is 8.17 (14)°. Within the urea unit, the N—H atoms are anti to each other and one of the N—H atoms forms an intramolecular N—H...N hydrogen bond. Helical supramolecular chains along [001] are formed via N—H...N(imidazole) hydrogen bonds in the crystal structure. These are connected into a three-dimensional architecture by C—H...O(carbonyl) and C—H...π interactions.